Low-carbon composite cementitious material based on grain composition and hydration thermodynamic characteristics and design method of low-carbon composite cementitious material

By combined with the combined design of low -carbon composite gel materials, combined with granular matching and hydrophilic thermodynamic characteristics, the problem of low design efficiency and not fully utilizing physical and chemical characteristics in existing technologies, realizing high performance and low -carbon Composite gel material.

CN119361038APending Publication Date: 2025-01-24TONGJI UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411375049.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The prior art has problems in the mix ratio design of low-carbon composite cementitious materials with low design efficiency and insufficient utilization of the physical and chemical characteristics of the cementitious materials, making it difficult to achieve low-carbon and high-performance concrete materials.

Method used

Adopting a design method based on the characteristics of granular grade and hydration thermodynamics, through the design of hydrophilic thermodynamics simulation and Dinger-FUNK model design, collaborate to determine the cooperation ratio of composite gel materials, optimize the particle size distribution of gel materials and the active chemical components Coordinated enhancement.

Benefits of technology

A large mixing auxiliary gel material replaces silicate cement, which improves the mechanical performance and durability of composite gel materials. At the same time, it has significantly reduced carbon emissions and has significant carbon reduction benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361038A_ABST
    Figure CN119361038A_ABST
Patent Text Reader

Abstract

The invention relates to a low-carbon composite cementitious material based on grain composition and hydration thermodynamic characteristics and a design method, and the design method comprises the following steps: 1) determining the reaction degree and active chemical components of an auxiliary cementitious material, carrying out mass normalization on main active components, and determining the particle size distribution of cement and the auxiliary cementitious material; (2) determining a corresponding relation between the active components and the upper limit of the mixing amount according to the change rule of hydration products of the active components in different proportions and the Portland cement, and taking the corresponding relation as a hydration thermodynamic constraint condition; 3) designing close packing gradation of the cement and the auxiliary cementing material as a particle gradation constraint condition; 4, under the condition of synergistic constraint of hydration thermodynamics and grain composition, the mix proportion of the low-carbon composite cementing material.Portland cement can be replaced by a large-mixing-amount auxiliary cementing material, the mix proportion design of the low-carbon composite cementing material is guided, and obvious carbon reduction benefits are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and relates to a low-carbon composite cementitious material based on particle grading and hydration thermodynamic characteristics and a design method. Background Art

[0002] Under my country's "dual carbon" strategy, the construction industry is gradually transforming towards energy conservation and low carbon development. To achieve the goal, more effective carbon reduction measures need to be explored to achieve zero carbon emissions in buildings. From the perspective of concrete materials, carbon emissions mainly come from cementitious materials, especially cement, and 70% of carbon emissions come from cement production. Therefore, the core issue of low carbon is how to reduce the amount of cement, actively use auxiliary cementitious materials such as fly ash, mineral powder and silica fume to reduce carbon emissions. On the other hand, from the perspective of the mix ratio of composite cementitious materials, optimize the mix ratio and improve the performance of concrete, thereby reducing carbon emissions under the functional unit.

[0003] The current standard mix design method is mainly based on semi-empirical and semi-quantitative calculation design based on the performance law of concrete, which requires trial mixing experiments for verification and adjustment. In pursuit of low carbon emissions and high performance, the current standard mix design method has gradually shown limitations in design efficiency and other aspects. In addition, the existing technology rarely considers the physical and chemical characteristics of cementitious materials, such as particle size distribution, particle morphology, active chemical components and reaction activity. On the one hand, the gradation curve of the composite of silicate cement and auxiliary cementitious materials such as fly ash and mineral powder is designed by using a close-packed gradation model, which can improve the packing density and improve the mechanical properties and durability of the composite cementitious materials; on the other hand, the hydration thermodynamics is used to study the synergistic enhancement effect of the active components between auxiliary cementitious materials, determine the upper limit of the dosage of auxiliary cementitious materials, and reduce the dosage of silicate cement. The mix ratio of composite cementitious materials can be obtained through the coordinated design of hydration thermodynamics and particle grading. Therefore, it is necessary to develop a low-carbon composite cementitious material design method based on particle grading and hydration thermodynamic characteristics to reduce the amount of cement component in cementitious materials, increase the proportion of auxiliary cementitious materials replacing silicate cement, achieve synergistic enhancement and close stacking between the components of composite cementitious materials, ensure the performance requirements of concrete, and achieve the effect of energy saving and carbon reduction, providing certain theoretical and technical support for the low-carbon development of the concrete industry. Summary of the invention

[0004] In view of the above-mentioned defects of the prior art, the present invention provides a low-carbon composite cementitious material and a design method based on particle grading and hydration thermodynamic characteristics. In terms of chemistry, the hydration thermodynamic characteristics between silicate cement and auxiliary cementitious materials are considered; in terms of physics, the close stacking gradation of cementitious materials is considered. The design of the mix ratio of composite cementitious materials is guided by both chemical and physical aspects. In terms of chemistry, the change law of the hydration reaction products after the auxiliary cementitious materials are added to silicate cement is studied according to hydration thermodynamics, and the corresponding relationship between the active components SiO2, Al2O3 and CaO and the upper limit of the auxiliary cementitious material dosage is obtained; in terms of physics, the grading curve of silicate cement and auxiliary cementitious materials such as fly ash and mineral powder is designed according to the Dinger-Funk model, so that the grading curve of the composite cementitious material conforms to the ideal grading curve to the greatest extent, and the stacking density is improved. The mix ratio of the composite cementitious material is obtained by the coordinated design of hydration thermodynamics and particle grading, and the low carbon and high performance of the composite cementitious material are jointly achieved.

[0005] In order to achieve the above object, on the one hand, the present invention provides a method for designing a low-carbon composite cementitious material based on particle grading and hydration thermodynamic characteristics, characterized in that it comprises the following steps:

[0006] 1) Determine the physical and chemical characteristics of cementitious materials: quantitatively analyze the content of active chemical components of auxiliary cementitious materials, determine the degree of reaction of auxiliary cementitious materials added to silicate cement, and determine the particle size distribution curves of silicate cement and auxiliary cementitious materials;

[0007] 2) Determine the hydration thermodynamic constraints: Use hydration thermodynamic simulation to obtain the change law of hydration products of SiO2, Al2O3 and CaO components with different proportions and silicate cement. According to the consumption degree of calcium hydroxide in the simulated hydration product, determine the corresponding relationship between SiO2, Al2O3 and CaO components and the upper limit of the dosage as the hydration thermodynamic constraints;

[0008] 3) Determine the particle gradation constraints: Use the Dinger-Funk model to design the close packing gradation of silicate cement and auxiliary cementitious materials: According to the least squares method, the gradation curve of the composite cementitious material Ideal gradation curve of Dinger-Funk model The deviation of is the smallest, which is used as the particle grading constraint condition; In the formula, for and The minimum square difference of is the gradation curve of composite cementitious materials; is the ideal gradation curve of Dinger-Funk model;

[0009] 4) Under the coordinated constraints of hydration thermodynamics and particle gradation, the planning solver is used to design the mix proportion of low-carbon composite cementitious materials that simultaneously meets the constraints of hydration thermodynamics and particle gradation.

[0010] Furthermore, the active chemical components described in step 1) are chemical components of the amorphous phase of the auxiliary cementitious material. The specific chemical component content of the amorphous phase in the auxiliary cementitious material is quantitatively calculated by XRF and XRD; the reaction degree of the auxiliary cementitious material added to the silicate cement is determined by a selective dissolution method; and the particle size distribution curves of the silicate cement and the auxiliary cementitious material are determined by a laser particle size analyzer. It is understood that the chemical component content and the particle size distribution curve can also be determined by other known methods that meet the determination requirements.

[0011] Furthermore, the selective dissolution method is that EDTA-alkaline solution selectively dissolves hydration products and auxiliary cementitious materials, completely dissolving silicate cement and hydration products, while volcanic ash materials such as silica fume and fly ash are almost not dissolved, thereby separating unreacted auxiliary cementitious materials and calculating the reaction degree of the auxiliary cementitious materials.

[0012] Furthermore, in step 1), the particle size distribution curve is measured by a laser particle size analyzer, and the characteristic particle size value D5 is selected as the minimum particle size D of the gelling material. min , D 95 As the maximum particle size D max For Dinger-Funk model gradation design, D x It is expressed as the particle size value corresponding to x% on the cumulative particle size distribution curve.

[0013] Furthermore, in step 2), the hydration product calcium hydroxide participates in the pozzolanic reaction of the auxiliary cementitious material. When the calcium hydroxide is consumed, the pozzolanic reaction of the auxiliary cementitious material is hindered, which is not conducive to the stable development of strength. When the hydration product Ca(OH)2 is consumed as the dosage increases, the corresponding dosage serves as the upper limit of the dosage under the ratio of SiO2, Al2O3 and CaO.

[0014] Furthermore, in step 4), under the synergistic constraints of hydration thermodynamics and particle gradation, the process of using planning solver to calculate the mix ratio of the composite cementitious material includes three parts: target value, control value, and boundary conditions; the target value is the minimum deviation between the gradation curve of the composite cementitious material and the ideal gradation curve, and at the same time, the active chemical components of the composite auxiliary cementitious material must be within the thermodynamic constraints; the control value is the volume fraction of the cementitious material ( ), which affects the grading curve of composite cementitious materials and the active chemical components of composite auxiliary cementitious materials. Achieve the target value; boundary conditions are limiting conditions in the solution process, which can limit the control value and the target value and reflect the actual limiting conditions of the engineering application, as shown in the following formula. More stringent constraints include concrete standards or special requirements of the project:

[0015]

[0016] After determining the target value, control value and boundary conditions, the planning solution obtains the solution that satisfies the hydration thermodynamics and particle grading constraints. , and then calculate the mix ratio of low-carbon composite cementitious materials that meets the constraints of hydration thermodynamics and particle grading.

[0017] On the other hand, the present invention provides a low-carbon composite cementitious material, characterized in that it is prepared by designing a raw material ratio using the low-carbon composite cementitious material design method based on particle grading and hydration thermodynamic characteristics as described above.

[0018] Compared with the prior art, the above invention has the following advantages or beneficial effects:

[0019] (1) The low-carbon composite cementitious material design method based on particle grading and hydration thermodynamic characteristics of the present invention provides a new low-carbon composite cementitious material design method based on the synergy of chemistry and physics, and provides a new idea for the design of the mix ratio of low-carbon composite cementitious materials;

[0020] (2) The low-carbon composite cementitious material design method based on particle grading and hydration thermodynamic characteristics of the present invention determines the constraint conditions required for the design of the low-carbon composite cementitious material mix ratio from a theoretical level, and the design is more reasonable;

[0021] (3) The low-carbon composite cementitious material design method based on particle grading and hydration thermodynamic characteristics of the present invention has advantages in carbon reduction benefits and good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 A flow chart of a method for designing a low-carbon composite cementitious material of the present invention;

[0023] Figure 2 is the particle size distribution diagram of silicate cement and auxiliary cementitious materials;

[0024] Figure 3 It is the contour map of the upper limit of different SiO2, Al2O3 and CaO dosage under hydration thermodynamic simulation;

[0025] Figure 4 This is the relationship diagram between fly ash, mineral powder, silica fume and the upper limit of the dosage;

[0026] Figure 5Grading curves of composite cementitious materials under the synergistic constraints of hydration thermodynamics and grading ((a) P-1; (b) P-2; (c) P-3). DETAILED DESCRIPTION

[0027] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. The following content is helpful for those skilled in the art to further understand the present invention, but is not intended to limit the present invention.

[0028] Example

[0029] See attached Figure 1 This embodiment provides a method for designing a low-carbon composite cementitious material based on particle grading and hydration thermodynamic characteristics, comprising the following steps:

[0030] (1) Determine the physical and chemical characteristics of cementitious materials

[0031] The particle size distribution curves of Portland cement (C), fly ash (FA), silica fume (SF) and mineral powder (SL) were measured using a laser particle size analyzer. Anhydrous ethanol was selected as the dispersant. The test results are shown in the attached Figure 2 As shown. Select the characteristic particle size value D5 as the minimum particle size D min , D 95 As the maximum particle size D max For Dinger-Funk model gradation design, D x It is expressed as the particle size value corresponding to x% on the cumulative particle size distribution curve.

[0032] Portland cement, fly ash, silica fume and mineral powder were ground using an agate mortar and passed through a 200-mesh sieve to obtain powder samples. The chemical composition of each cementitious material was measured using an X-ray fluorescence spectrometer (XRF).

[0033] The XRD internal standard method was used to quantitatively determine the amorphous phase content of fly ash, silica ash and mineral powder. 20% mass fraction of α-crystalline alumina was added to the fly ash, silica ash and mineral powder samples as an internal standard and mixed evenly. HighScorePlus software was used to quantitatively analyze the amorphous phase content of the samples, and the amorphous phase content of fly ash, silica ash and mineral powder and the corresponding chemical component content were calculated, as shown in Table 1.

[0034] Table 1 Amorphous phase content and corresponding chemical component content of fly ash, silica fume and mineral powder

[0035] Group CaO <![CDATA[Al2O3]]> <![CDATA[SiO2]]> MgO <![CDATA[Fe2O3]]> <![CDATA[Na2O]]> <![CDATA[SO3]]> <![CDATA[K2O]]> ZnO Amorphous C 64.08 4.50 20.61 0.64 3.18 0.08 2.61 0.86 0.05 / SF 0.32 0.19 94.02 0.56 0.10 0.19 1.27 0.32 0.01 98.5 FA 11.68 20.04 52.40 0.97 6.71 1.87 0.16 3.34 0.05 84.6 SL 50.61 13.93 21.10 6.18 1.22 0.35 1.70 0.50 \ 57.5

[0036] EDTA-alkaline solution was selected to determine the degree of reaction of fly ash, silica ash and mineral powder in cement. EDTA-alkaline solution can dissolve silicate cement and hydration products, while volcanic ash materials such as mineral powder and fly ash are almost not dissolved. The unreacted auxiliary cementitious materials can be separated and the degree of reaction of the auxiliary cementitious materials can be calculated. The water-cement ratio of the pure slurry was set to 0.3, fly ash and mineral powder were mixed at 37% and 50%, and silica ash and mineral powder were mixed at 40% and 50%, and cured to 56 days. The cement and hydration products were dissolved by EDTA-alkaline solution, and the unreacted fly ash, silica ash and mineral powder were filtered and separated. After drying, they were cooled to room temperature, and the degree of reaction of the auxiliary cementitious materials under mixed mixing for 56 days was calculated.

[0037] (2) Determine the thermodynamic constraints of hydration

[0038] It can be seen from Table 1 that the chemical components of fly ash, silica fume and mineral powder are mostly SiO2, Al2O3 and CaO, and other chemical components such as Fe2O3, Na2O, K2O, etc. have low contents and are omitted. In the SiO2-Al2O3-CaO ternary diagram, different proportions of SiO2, Al2O3 and CaO components are used to represent various types of auxiliary cementitious materials.

[0039] When fly ash, silica fume and mineral powder are added to silicate cement, the active chemical components SiO2, Al2O3 and CaO mainly participate in the hydration reaction of cement. Therefore, in the hydration thermodynamic simulation process, different proportions of SiO2, Al2O3 and CaO components are input, as shown in Table 2.

[0040] Table 2 Input ratio of SiO2, Al2O3 and CaO components in each experimental group

[0041] Group <![CDATA[SiO2]]> <![CDATA[Al2O3]]> CaO 1 0.00 0.00 1.00 2 0.00 0.50 0.50 3 0.00 1.00 0.00 4 0.10 0.10 0.80 5 0.10 0.40 0.50 6 0.10 0.80 0.10 7 0.20 0.20 0.60 8 0.20 0.30 0.50 9 0.20 0.40 0.40 10 0.20 0.60 0.20 11 0.30 0.50 0.20 12 0.33 0.33 0.34 13 0.40 0.10 0.50 14 0.40 0.20 0.40 15 0.40 0.40 0.20 16 0.40 0.50 0.10 17 0.50 0.00 0.50 18 0.50 0.30 0.20 19 0.50 0.50 0.00 20 0.60 0.20 0.20 21 0.80 0.10 0.10 22 1.00 0.00 0.00

[0042] The hydration thermodynamics GEMS was used to simulate the change of hydration products of silicate cement with different proportions of SiO2, Al2O3 and CaO components, and the upper limit of the dosage under the corresponding SiO2, Al2O3 and CaO ratio was further determined.

[0043] Fly ash, silica fume and mineral powder added to cement participate in the hydration reaction of cement by relying on volcanic ash activity and hydraulic hardness, and require the hydration product calcium hydroxide to stimulate the volcanic ash reaction to generate secondary CSH gel. When the simulated hydration product calcium hydroxide is consumed, it is assumed that fly ash, silica fume and mineral powder no longer participate in the hydration reaction of cement. Therefore, the dosage of auxiliary cementitious materials can be regulated according to the content of calcium hydroxide produced in the composite cementitious material system. According to the consumption degree of calcium hydroxide simulated by hydration thermodynamics, the corresponding relationship between SiO2, Al2O3 and CaO components and the upper limit of dosage is determined, as shown in the attached figure. Figure 3The reaction degree of fly ash, silica fume and mineral powder measured in actual application is introduced into the hydration thermodynamic simulation to obtain the corrected corresponding relationship between fly ash, mineral powder, silica fume and the upper limit of the dosage, as shown in the attached figure. Figure 4 As shown, it serves as a hydration thermodynamic constraint.

[0044] According to the attached Figure 4 The upper limit of the dosage and the corresponding ratio of SiO2, Al2O3 and CaO are used as hydration thermodynamic constraints to design the mix ratio of composite cementitious materials.

[0045] Set the hydration thermodynamic constraint conditions: the upper limit range of the auxiliary cementitious material content in the composite cementitious material mix ratio is 46.3~70.1%, and the boundary ranges of SiO2, Al2O3 and CaO components corresponding to fly ash, silica fume and mineral powder are SiO2: 0.246~0.995; Al2O3: 0.002~0.238; CaO: 0.003~0.591. The specific hydration thermodynamic constraint expressions are as follows:

[0046] Upper limit of auxiliary cementitious material dosage:

[0047]

[0048] SiO2 component ratio range:

[0049]

[0050] Al2O3 component ratio range:

[0051]

[0052] CaO component ratio range:

[0053]

[0054] Where: is the total mass fraction of auxiliary cementitious materials in the composite cementitious material; , , are the mass fractions of fly ash, silica fume and mineral powder in the auxiliary cementitious materials; , , They are the proportions of SiO2, Al2O3 and CaO in fly ash; , , They are the proportions of SiO2, Al2O3 and CaO in silica ash; , , They are the proportions of SiO2, Al2O3 and CaO in the mineral powder respectively.

[0055] (3) Determine the particle size distribution constraints

[0056] Composite cementitious materials are composed of silicate cement and auxiliary cementitious materials such as fly ash, silica fume, and mineral powder. The particle volume fraction of can be expressed by formula (5), which is affected by the particle size and dosage of the cementitious material. According to formula (6), the particle size smaller than The cumulative volume fraction ( Based on formula (5) and (6), it is simplified to formula (7). The grading calculation is performed according to the particle size distribution data of the cementitious material measured by the laser particle size analyzer to obtain the cumulative volume fraction of the composite cementitious material ( ).

[0057]

[0058]

[0059]

[0060] Where: The particle size of the composite cementitious material is Volume fraction of It is a material in composite cementitious materials Volume fraction of It is a cementitious material The median particle size is Volume fraction of It is a cementitious material Apparent density, kg / m 3 ; The particle size of the composite cementitious material is less than The cumulative volume fraction of It is a cementitious material Medium particle size less than The cumulative volume fraction.

[0061] According to the particle size distribution data of the cementitious material measured by the laser particle size analyzer, the particle size smaller than The cumulative volume fraction ( ).

[0062] Cumulative volume fraction of composite cementitious materials ( ) and the ideal cumulative score ( ) has a gap, the Dinger-Funk model is used to design the close packing gradation of cement and auxiliary cementitious materials, so that the deviation between the gradation curve of composite cementitious materials and the ideal gradation curve of the Dinger-Funk model is minimized. More specifically, the least squares method is used to and ) square of the difference ( ) is minimized, as shown in formula (8), which serves as the particle size distribution constraint of the cementitious material.

[0063]

[0064] (4) Planning solution

[0065] Under the synergistic constraints of hydration thermodynamics and particle grading, the planning solution is used to clarify the target value, control value, and boundary conditions, and the volume fraction of cementitious materials (Portland cement, fly ash, silica fume, and mineral powder) is calculated ( ).

[0066] The target value is the minimum deviation between the gradation curve of the composite cementitious material and the ideal gradation curve. At the same time, it must also satisfy the thermodynamic constraints of the active chemical components of the composite auxiliary cementitious material, that is, the ( )and( ) is minimized, while also ensuring that the active chemical components of the composite auxiliary cementitious material are within thermodynamic constraints.

[0067] The control value is the volume fraction of cementitious material ( ), which affects the grading curve of composite cementitious materials and the active chemical components of composite auxiliary cementitious materials. Achieve target value.

[0068] Boundary conditions are limiting conditions in the solution process, which can limit the control value and target value and reflect the actual limiting conditions of engineering applications, as shown in formula (9). More stringent constraints include concrete standards or special requirements of the project.

[0069]

[0070] After determining the target value, control value and boundary conditions, the planning solution obtains the solution that satisfies the hydration thermodynamics and particle grading constraints. , and then calculate the mix ratio of low-carbon composite cementitious materials that meets the constraints of hydration thermodynamics and particle grading.

[0071] The mix ratio of the low-carbon composite cementitious material calculated by the process of the present invention is listed in Table 3. In order to show the amount of silicate cement (C), fly ash (FA), silica fume (SF), and mineral powder (SL), the mix ratio is expressed in mass fraction.

[0072] Table 3 Calculated mix ratio of low carbon composite cementitious materials

[0073]

[0074] The composite cementitious material grading curve obtained by the low-carbon composite cementitious material design method based on particle grading and hydration thermodynamic characteristics of this embodiment is shown in the attached figure. Figure 5 As shown in the figure, by adjusting the proportion of cementitious materials through planning and solving, the gradation curve (Optimal curve) of composite cementitious materials is better in line with the ideal gradation curve (Ideal curve), achieving a dense stacking state; the corresponding auxiliary cementitious material dosage and chemical composition also meet the thermodynamic constraints.

[0075] From the above description, it can be seen that the low-carbon composite cementitious material design method based on particle grading and hydration thermodynamic characteristics of the present invention provides a new idea for the design of low-carbon composite cementitious material mix proportions, realizes the replacement of silicate cement with a large amount of auxiliary cementitious materials, has significant carbon reduction benefits, and has good application prospects.

[0076] In summary, the present invention provides a design method for low-carbon composite cementitious materials based on particle grading and hydration thermodynamic characteristics, and the steps are as follows: 1) determining the reaction degree and active chemical components of auxiliary cementitious materials such as fly ash, silica fume and mineral powder, normalizing the mass of the main active components SiO2, Al2O3 and CaO, and determining the particle size distribution of cement and auxiliary cementitious materials; 2) using hydration thermodynamics GEMS simulation to obtain the change law of hydration products of SiO2, Al2O3 and CaO components in different proportions and silicate cement, and determining the corresponding relationship between SiO2, Al2O3 and CaO components and the upper limit of the dosage as a hydration thermodynamic constraint condition; 3) using the Dinger-Funk model to design the close stacking gradation of cement and auxiliary cementitious materials, so that the deviation between the grading curve of the composite cementitious material and the ideal grading curve of the Dinger-Funk model is minimized, as a particle grading constraint condition; 4) under the conditions of hydration thermodynamics (chemistry) and particle grading (physics) synergistic constraints, using planning and solving to design the mix ratio of the low-carbon composite cementitious materials. The present invention can realize the replacement of silicate cement with a large amount of auxiliary cementitious materials, provide guidance for the design of the mix ratio of low-carbon composite cementitious materials, and has significant carbon reduction benefits.

[0077] Those skilled in the art should understand that those skilled in the art can implement variations by combining the prior art and the above embodiments, which will not be described in detail here. Such variations do not affect the essential content of the present invention, and will not be described in detail here.

[0078] The above describes the preferred embodiments of the present invention. It should be understood that the present invention is not limited to the above-mentioned specific embodiments, and the devices and structures that are not described in detail should be understood to be implemented in a common manner in the art; any technician familiar with the art can use the above-disclosed methods and technical contents to make many possible changes and modifications to the technical solutions of the present invention without departing from the scope of the technical solutions of the present invention, or modify them into equivalent embodiments of equivalent changes, which does not affect the essential content of the present invention. Therefore, any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solutions of the present invention are still within the scope of protection of the technical solutions of the present invention.

Claims

1. A design method for low-carbon composite cementitious materials based on particle grading and hydration thermodynamic characteristics, characterized in that: The steps include: 1) Determine the physical and chemical characteristics of cementitious materials: quantitatively analyze the content of active chemical components of auxiliary cementitious materials, determine the degree of reaction of auxiliary cementitious materials added to silicate cement, and determine the particle size distribution curves of silicate cement and auxiliary cementitious materials; 2) Determine the hydration thermodynamic constraints: Use hydration thermodynamic simulation to obtain the change law of hydration products of SiO2, Al2O3 and CaO components with different proportions and silicate cement. According to the consumption degree of calcium hydroxide in the simulated hydration product, determine the corresponding relationship between SiO2, Al2O3 and CaO components and the upper limit of the dosage as the hydration thermodynamic constraints; 3) Determine the particle gradation constraints: Use the Dinger-Funk model to design the close packing gradation of silicate cement and auxiliary cementitious materials: According to the least squares method, the gradation curve of the composite cementitious material Ideal gradation curve of Dinger-Funk model The deviation of is the smallest, which is used as the particle grading constraint condition; The calculation formula is: In the formula, for and The minimum square difference of is the gradation curve of composite cementitious materials; is the ideal gradation curve of Dinger-Funk model; 4) Under the coordinated constraints of hydration thermodynamics and particle gradation, the planning solver is used to design the mix proportion of low-carbon composite cementitious materials that simultaneously meets the constraints of hydration thermodynamics and particle gradation.

2. A method for designing low-carbon composite cementitious materials based on particle grading and hydration thermodynamic characteristics according to claim 1, characterized in that: The active chemical components described in step 1) are chemical components of the amorphous phase of the auxiliary gelling material, and the specific chemical component content of the amorphous phase in the auxiliary gelling material is quantitatively calculated by XRF and XRD; The selective dissolution method is used to determine the reaction degree of the auxiliary cementitious material added into the silicate cement; the laser particle size analyzer is used to determine the particle size distribution curves of the silicate cement and the auxiliary cementitious material.

3. A method for designing low-carbon composite cementitious materials based on particle grading and hydration thermodynamic characteristics according to claim 2, characterized in that: The selective dissolution method is that EDTA-alkali solution selectively dissolves hydration products and auxiliary cementitious materials, completely dissolving silicate cement and hydration products, while volcanic ash materials such as silica fume and fly ash are almost not dissolved, thereby separating unreacted auxiliary cementitious materials and calculating the reaction degree of the auxiliary cementitious materials.

4. A method for designing low-carbon composite cementitious materials based on particle grading and hydration thermodynamic characteristics according to claim 2, characterized in that: In step 1), the particle size distribution curve is measured by a laser particle size analyzer, and the characteristic particle size value D5 is selected as the minimum particle size D of the gelling material. min , D 95 As the maximum particle size D max For Dinger-Funk model gradation design, D x It is expressed as the particle size value corresponding to x% on the cumulative particle size distribution curve.

5. The method for designing low-carbon composite cementitious materials based on particle grading and hydration thermodynamic characteristics according to claim 1, characterized in that: In step 2), the hydration product calcium hydroxide participates in the pozzolanic reaction of the auxiliary cementitious material. When the calcium hydroxide is consumed, the pozzolanic reaction of the auxiliary cementitious material is hindered, which is not conducive to the stable development of strength. When the hydration product Ca(OH)2 is consumed as the dosage increases, the corresponding dosage serves as the upper limit of the dosage under the ratio of SiO2, Al2O3 and CaO.

6. The method for designing low-carbon composite cementitious materials based on particle grading and hydration thermodynamic characteristics according to claim 1, characterized in that: In step 4), under the synergistic constraints of hydration thermodynamics and particle grading, the process of using planning solver to calculate the mix ratio of composite cementitious materials includes three parts: target value, control value, and boundary conditions; The target value is the minimum deviation between the gradation curve of the composite cementitious material and the ideal gradation curve, and at the same time, the active chemical components of the composite auxiliary cementitious material must be within the thermodynamic constraints; The control value is the volume fraction of cementitious material ( ), which affects the grading curve of composite cementitious materials and the active chemical components of composite auxiliary cementitious materials. Achieve the target value; boundary conditions are limiting conditions in the solution process, which can limit the control value and the target value and reflect the actual limiting conditions of the engineering application, as shown in the following formula: After determining the target value, control value and boundary conditions, the planning solution obtains the solution that satisfies the hydration thermodynamics and particle grading constraints. , and then calculate the mix ratio of low-carbon composite cementitious materials that meets the constraints of hydration thermodynamics and particle grading.

7. A low-carbon composite cementitious material, characterized in that: The raw material ratio is designed and prepared by adopting the low-carbon composite cementitious material design method based on particle grading and hydration thermodynamic characteristics as described in any one of claims 1 to 6.

Citation Information

Cited By

  • Component proportion design method and production system for all-solid waste slag-based cementing material

    CN121758083A

  • A method for designing component proportion of a full-solid-waste-slag-based cementitious material and a production system thereof

    CN121758083B